Assessment of titanium level in submucosal plaque around healthy implants and implants with peri-implantitis: A clinical study - Juzer Rasul; Manoj Kumar Thakur; Barkha Maheshwari; Nausheen Aga; Harsh Kumar; Monica Mahajani (Wolters Kluwer Medknow Publications, 2021)
Background: The present study focused on assessing the level of titanium in submucosal plaque in the peri-implant area with peri-implantitis in comparison to healthy implants. Methodology: Sixty patients with titanium dental implants were recruited. The degree of titanium in submucosal plaque around peri-implantitis and healthy implants was estimated using inductively coupled plasma mass spectrometry. Results: The mean ± standard deviation probing depth in Group I was 3.12 ± 1.1 and in Group II was 7.2 ± 2.5; gingival index was 0.64 ± 0.3 and 1.64 ± 0.8 in Group I and Group II, respectively. The plaque index was 0.82 ± 0.2 in Group I and 1.5 ± 0.6 in Group II. The mean plaque mass in Group I was 24.1 ± 3.8 ng/ul and 49.3 ± 6.4 ng/ul in Group II. The mean titanium level in Group I was 0.08 ± 0.02 μg and in Group II was 0.91 ± 0.04 μg. A highly significant difference between both groups was found (P < 0.05). Conclusion: There was a significantly higher titanium level in submucosal plaque around dental implants with signs of peri-implantitis as compared to healthy dental implants.